The sirac - contribution to the technology knowledge, composition and quality - Sonja Bijelac; Zlatan Sarić; Marko Stanišić (Mljekarstvo)
The Sirac is traditional cheese of Bosnia and Herzegovina, produced in the area of Tomislavgrad town. The taste is mild and moderately salty. It is consumed fresh, immediately upon production, or matured, after ripening. The technology is specific and according to that the Sirac can be classified as acid coagulated cheese. Milk proteins are coagulated by use of high temperature and acidity without adding of rennet. The aim of the work was to investigate traditional technology of the Sirac in small village households and to establish an optimal technology in order to apply it to industrial production. For this purpose, a ten tries in laboratory condition were done. The chemical composition of cheese milk, whey, fresh and ripened cheese was determined. During experiments all steps in technological process were followed. Special attention was paid to temperature and acidity of milk coagulation, draining of whey and pressing. Cheese was sensory evaluated after ripening period. The sensorial quality was good. Average score for all ten cheeses was 18.3 points and 5 samples were classified as extra and 5 as 1st class. The yield ranged from 12.25 to 17.76 % and showed that distribution of components to cheese was high. The analyses of whey confirmed this finding.